MODERN DIRECTIONS OF EDUCATIONAL WORK WITH CONSUMERS ON THE PART OF PORK PRODUCERS BASED ON THE ‘TRANSPARENT PIG FARM’ CONCEPT - Ivan Yu. Svinarev (Siberian Journal of Life Sciences and Agriculture, 2022)
Over the past 10–15 years, there has been a significant change in people’s access to information. The need for food manufacturers to understand consumers and their motivation in choosing a product has increased. This research aims to analyze the relevance and applicability of the transparent production concept in the conditions of the Russian Federation and identify the most significant problems for educational work. The research tasks are as follows: (1) comparing preferences of consumers buying meat in Russia and the USA; (2) studying the differences in the perception of visual information and attitudes towards industrial production depending on the level of competence; (3) analyzing key aspects of pork production that are of the greatest interest to consumers; and (4) analyzing existing tools for communicating with consumers. The following research methods were used to solve the tasks set: (1) theoretical (analysis, synthesis, generalization, and comparison of information on the research problem); (2) empirical (questioning, conversation, and content analysis); and (3) statistical (graphical and tabular interpretations of research data). The paper compares new data on the differences in preferences of consumers buying meat. Within the transparent production concept, the nine most relevant areas for educational work aimed at increasing mutual understanding between consumers and producers of meat products are identified. The analysis has shown that depending on the experience and knowledge of the biological characteristics of pigs, there is a fundamental difference in the assessment of animal welfare in specific production conditions. The following areas are identified as the most relevant for educational work: (1) environmental protection measures; (2) measures to reduce odors; (3) outdoor and indoor production; (4) fixed or free housing of gestating sows; (5) castration, cutting tails, and grinding fangs; (6) practice of using antibiotics; (7) practice of using growth stimulants; (8) nature of rapid growth and reaching slaughter condition; and (9) animal welfare. As the main tools for information communication with consumers, it is proposed to more actively using social networks, company websites on the Internet, television and radio, press publications, and agritourism, as well as agroclasses and agrohours at schools.